2021
DOI: 10.1108/oir-07-2020-0282
|View full text |Cite
|
Sign up to set email alerts
|

Message sharing and verification behaviour on social media during the COVID-19 pandemic: a study in the context of India and the USA

Abstract: PurposeTechnology has eased access to information. During the ongoing COVID-19 pandemic, ease of access and transmission of information via social media has led to ambiguity, misinformation and uncertainty. This research studies the aforementioned behaviours of information sharing and verification related to COVID-19, in the context of social media.Design/methodology/approachTwo studies have been carried out. Study 1, with Indian social media users, is a two-factor between-subjects experimental design that inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
(87 reference statements)
0
21
1
Order By: Relevance
“…On the other hand, the mediation effect showed that anxiety triggered unverified information sharing. Compared with previous research that identified anxiety as a predictor of information sharing (Thelwall and Thelwall, 2020;Yin et al, 2020;Sharma and Kapoor, 2021), our findings demonstrated that anxiety also predicted unverified information sharing. Moreover, the findings also supported that unverified information sharing functioned as a coping strategy for individuals to deal with emotional distress (Lazarus and Folkman, 1984) during the pandemic.…”
Section: Theoretical Implicationscontrasting
confidence: 95%
See 1 more Smart Citation
“…On the other hand, the mediation effect showed that anxiety triggered unverified information sharing. Compared with previous research that identified anxiety as a predictor of information sharing (Thelwall and Thelwall, 2020;Yin et al, 2020;Sharma and Kapoor, 2021), our findings demonstrated that anxiety also predicted unverified information sharing. Moreover, the findings also supported that unverified information sharing functioned as a coping strategy for individuals to deal with emotional distress (Lazarus and Folkman, 1984) during the pandemic.…”
Section: Theoretical Implicationscontrasting
confidence: 95%
“…To manage anxiety and reduce emotional distress, people share information with their family, friends, co-workers, and community members to feel connected to close others (Chen et al, 2021;Lim et al, 2021). The positive association between anxiety and information sharing on social media has been empirically supported in previous research (Thelwall and Thelwall, 2020;Yin et al, 2020;Sharma and Kapoor, 2021). Because individuals in an anxious state are likely to make careless decisions during public health emergencies (Moghanibashi-Mansourieh, 2020), their information-sharing behaviors are often characterized by a lack of verification.…”
Section: The Mediating Role Of Anxietymentioning
confidence: 80%
“…Contrary to the idea that original rumors spread face-to-face, the number, spread speed, and scope of influence of online rumors are constantly expanding in the internet age due to the rapid advancement in internet technology and the continuous growth of social media users ( Bloch et al, 2017 ). However, the ease with which information may be accessed and transmitted through social media has resulted in ambiguity, misinformation, and doubt ( Sharma and Kapoor, 2022 ). Moreover, internet rumors are anonymous, interactive, and free of charge; this reduces the spread of psychological and material costs and promotes the spread of rumors ( Difonzo, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, researchers are highlighting issues related to the sharing of fake news—including that pertaining to COVID-19—on social media (Apuke and Omar, 2021a; Barakat et al. , 2021; Sharma and Kapoor, 2022; Talwar et al. , 2019).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%